Natural Killer Cell Transcript 4 promotes the development of Sjӧgren's syndrome via activation of Rap1 on B cells. Issue 116 (January 2021) - Qu, Peng; Wuest, Todd; Min, Yongfen; Alevizos, Ilias; Young, Howard A.; Lin, P. Charles
Abstract: Autoimmune disorders are the third most common diseases in the United States, and affect the daily lives of millions of people. In this study, we analyzed patient samples, utilized a transgenic mouse model and human B cells to reveal Natural Killer Cell Transcript 4 (NK4) as a novel regulator that promotes the development of autoimmune disorders. NK4 was significantly elevated in samples from patients with Sjӧgren's Syndrome (SS). SS patients show elevated NK4 levels. There is a strong and positive correlation between the increased levels of NK4 and the duration of SS. Interestingly, transgenic expression of NK4 in a mouse model led to the development of autoantibodies and lymphocytic infiltration in salivary glands similar to those in SS patients. Those phenotypes were associated with increased B1a cells in the peritoneum, plasma cells in the spleen, and increased IgM, IgA, and IgG2a in serum of the NK4 transgenic mice. The autoimmune phenotypes became more severe in older mice. Moreover, after NK4 transfection, human naïve B cells were activated and memory B cells differentiation into IgG and IgA-plasmablasts, resulting in an increased production of autoantibodies.NK4 regulated the differentiation and activation of B cells through activating Rap1 activity. NK4 also promoted B cell migration in a paracrine fashion through an induction of CXCL13 in endothelial cells. Collectively, these findings identify NK4 as a promoter of the development of autoimmune disorders through its roles on B cells. Therefore, NK4 may be a novel therapeutic target for the treatment of autoimmune diseases. Highlights: NK4 promoted the development of Sjӧgren's Syndrome, as a novel regulator. Old NK4 transgenic mice developed autoantibodies and sialadenitis similar to those in Sjogren's Syndrome patients. NK4 induced B cell differentiation into plasma blasts to promote the development of Sjӧgren's Syndrome as a GEF for Rap1. NK4 promoted B cell migration through an induction of CXCL13 in surrounding inflammatory cells and endothelial cells.